2017
DOI: 10.1177/1708538117710845
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the conservative therapy for spontaneous isolated iliac artery dissection: Preliminary results

Abstract: Purpose To investigate the effectiveness of conservative therapy for spontaneous isolated iliac artery dissection (SIIAD). Methods From February 2006 to May 2016, all patients with SIIAD were included and analyzed. The diagnosis of SIIAD was made based on contrast-enhanced computed tomography. The imaging morphologic characteristics, treatments, and outcomes for each patient were analyzed. Results A total of 11 patients (10 male and 1 female, age 71.1 ± 7.8 years) were included in this study. Of the 11 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…In patients with asymptomatic isolated iliac artery dissection, conservative treatment was reported to be a safe option. 12 Open surgery can be suitable for patients with a strong desire to continue their sporting lifestyle. 1,9 Endovascular treatment has an advantage over open surgery in that it is less invasive, potentially making it preferable to athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with asymptomatic isolated iliac artery dissection, conservative treatment was reported to be a safe option. 12 Open surgery can be suitable for patients with a strong desire to continue their sporting lifestyle. 1,9 Endovascular treatment has an advantage over open surgery in that it is less invasive, potentially making it preferable to athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatments, which include close observation, follow‐up imaging, and best medical therapies, can be suitable for patients without symptoms. In patients with asymptomatic isolated iliac artery dissection, conservative treatment was reported to be a safe option 12 . Open surgery can be suitable for patients with a strong desire to continue their sporting lifestyle 1,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The study by Liang et al. reported that asymptomatic patients could be safely treated conservatively 12 . However, the question regarding further follow-up is still not answered.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular treatment is associated with high technical and clinical success rates with low periprocedural mortality and morbidity when compared with open repair 12 . The implantation of these devices can, in some cases, be limited by tortuosity of the iliac vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The main etiologies include especially collagen vascular disease, pregnancy and intense exercises in athletes [3,4]. Although several treatment options are available, including medical therapy, endovascular or open repair, there is actually no established consensus regarding optimal management of spontaneous iliac artery dissection [5][6][7]. We report the case of a 44 years old patient with no history of vascular diseases or trauma who was admitted in our institution for a spontaneous dissection of the right external iliac artery.…”
Section: Introductionmentioning
confidence: 99%